Do banks' overnight borrowing rates lead their CDS Price? evidence from the Eurosystem - Esa Jokivuolle; Eero Tölö; Matti Virén (European Central Bank (ECB), 2015)
We construct a measure of a bank's relative creditworthiness from Eurosystem's proprietary overnight loan data: the bank's “average overnight borrowing rate spread, relative to overnight rate index” (AOR). We investigate the dynamic relationship between the AOR and the credit default swap spread (CDS) of 60 banks in years 2008 - 2013. We find that in daily differences the AOR leads the CDS at least by one day. The lead is concentrated on days of market stress for banks which mainly borrow from “relationship” lender banks. Such borrower banks are typically smaller, have weak ratings, and likely reside in crisis countries. In longer differences, up to several weeks, both the AOR and the CDS have some predictive power over one another. In sum, overnight borrowing rates may provide additional early-warning indications on certain banks' deteriorating financial health over and above bank CDS spreads.
Keywords: G01; G14; G21; 330; credit default swaps (CDS); early-warning indicators; Eurosystem; leadlag relationship; money markets; overnight borrowing rates; TARGET2